Pengembangan E-Modul Berbasis Proyek untuk Meningkatkan Karakter Kreatif pada Siswa Kelas IV Sekolah Dasar - Fanehi Margaretha Zesy Fateha; Rizka Novi Irmaningrum; Oriza Zativalen (Universitas Negeri Medan, 2025)
This study aims to examine the validity, practicality, and effectiveness of a Project-Based E-module in enhancing the creative character of fourth-grade students in the P5 subject at elementary school. The research method used is Research and Development (R&D), employing the ADDIE development model, which consists of five main stages: Analysis, Design, Development, Implementation, and Evaluation. Data analysis techniques involved prerequisite tests and hypothesis testing. The results of the study show that: (1) the Project-Based E-Module is highly valid for use, based on the validation results from the subject matter expert with a score of 3.66 and the design expert with a score of 3.75, (2) the Project-Based E-Module is highly practical to use, as indicated by the student questionnaire results during the small group and large group trials, which obtained scores of 3.55 and 3.57 respectively. Student activity results in the small and large group trials received scores of 3.35 and 3.64, (3) the Project-Based E-Module is effective in improving the creative character of fourth-grade students, as evidenced by the T-test result of 0.000 and the N-Gain score of 64.87%, indicating a moderate level of achievement in the experimental class, and 24.19%, indicating a low level of achievement in the control class.